Liberação de nutrientes da palhada de forrageiras consorciadas com milho e sucessão com soja - Mendonca, Veridiana Zocoler de [UNESP]; Mano de Mello, Luiz Malcolm [UNESP]; Andreotti, Marcelo [UNESP]; Pariz, Cristiano Magalhaes [UNESP]; Yano, Elcio Hiroyoshi [UNESP]; Belchor Lages Pereira, Francisco Cezar [UNESP] (Soc Brasileira De Ciencia Do Solo, 2015)
In tropical regions there is rapid decomposition of plant material deposited on the soil, and the ability to recycle nutrients through this decomposition is one of the most important aspects of cover crops. The aim of this study was to evaluate the yield and nutrient release from forage crops intercropped with maize for silage, and soybean in succession. The study was conducted in the experimental area of Universidade Estadual Paulista, Ilha Solteira campus, Brazil. The experiment consisted of maize for silage intercropped with four forage species (Urochloa brizantha cv. Marandu, Urochloa ruziziensis, Panicum maximum cv. Tanzania, and Panicum maximum cv. Aries) sown in three modalities: in the maize row, together with fertilizer; broadcast at maize sowing; and broadcast in the V4 stage of maize, in a randomized block design in a 4 x 3 factorial arrangement with four replications. The evaluation of nutrient release was performed during the soybean cropping that followed the intercropping by the litter bag method at 30, 60, 90, and 120 days after sowing of soybean. Panicum maximum cv. Tanzania showed higher dry matter yield when sown by broadcasting at maize sowing. Sowing of forages in the maize row, and through broadcasting at maize sowing led to greater dry matter yield for straw formation. Intercropping of maize with forages in the autumn is an alternative for increasing the amount of straw and cycling of macronutrients in a no-till system. Potassium was the nutrient with the greatest accumulation in the forage straws (up to 150 kg ha(-1)), with 100 % release at 90 days after sowing soybean. The forage straws are thus an excellent alternative for cycling of this nutrient. Panicum maximum cv. Tanzania sown by broadcasting at the time of maize sowing showed greater phosphorus cycling (13 kg ha(-1)). Panicum maximum cv. Tanzania broadcast in the V4 stage of maize is the option with least potential for straw production and nutrient cycling, while the other options (forages and sowing modalities) have higher potential for use, at the criteria of machine availability for setting up intercropping with corn.

Em regiões de clima tropical ocorre rápida decomposição do material vegetal depositado sobre o solo, sendo a capacidade de reciclar nutrientes pela decomposição da palhada um dos aspectos mais importantes das plantas de cobertura. Objetivou-se avaliar a produtividade e a liberação de nutrientes de forrageiras consorciadas com milho para ensilagem, sucedido pela cultura da soja. Em área da Universidade Estadual Paulista, campus de Ilha Solteira, o experimento consistiu do consórcio de milho com quatro forrageiras: Urochloa brizantha cv. Marandu, Urochloa ruziziensis, Panicum maximum cv. Tanzânia e Panicum maximum cv. Áries, semeadas de três formas: na linha de semeadura do milho, misturada ao adubo; a lanço no mesmo dia da semeadura do milho; e a lanço no estádio V4 do milho, em delineamento de blocos casualizados com esquema fatorial 4 × 3 e quatro repetições. A avaliação da liberação de nutrientes foi realizada durante o cultivo da soja em sucessão aos consórcios pelo método do litter bag, aos 30, 60, 90 e 120 após a semeadura da soja. Panicum maximum cv. Tanzânia apresentou maior produtividade de matéria seca quando semeada a lanço por ocasião da semeadura do milho. A semeadura das forrageiras na linha do milho e a lanço simultaneamente ao milho proporcionaram maior produtividade de matéria seca para formação de palhada. O consórcio da cultura do milho com forrageiras no outono é alternativa para elevar a quantidade de palhada e ciclagem de macronutrientes em sistema plantio direto. O K foi o nutriente que apresentou maior acúmulo na palhada das forrageiras (até 150 kg ha-1), com 100 % de liberação aos 90 dias após a semeadura da soja, sendo excelente alternativa de ciclagem desse nutriente. Panicum maximum cv. Tanzânia semeada a lanço simultaneamente ao milho se destacou na ciclagem de P (13 kg ha-1). Panicum maximum cv. Tanzânia distribuída a lanço no estádio V4 do milho é a opção com menor potencial para produção de palhada e ciclagem de nutrientes, enquanto as demais opções (forrageiras e modalidades de semeadura) têm maior potencial de utilização, ficando a critério da disponibilidade dos maquinários para implantação do consórcio com a cultura do milho.
Nutrient release from forage straw intercropped with maize and followed by soybean
Keywords: No-till system; Corn; Nutrient cycling; Urochloa; Panicum; Low altitude tropical savanna